Composition of the Essential Oil of Some Centaurea L. - Akkurt, A.; Celik, S. (ASIAN JOURNAL OF CHEMISTRY, 2014)
Composition of the water-distilled oil of Centaurea kurdica, C. antochia var. antochia and Centaurea albonitens in Turkey, were analyzed by GC and GC-MS. In essential oil of Centaurea kurdica, caryophyllene 14.4 %, a - humulene 4.62 %; germacrene 11.95 %; beta-farnesene 9.78 %; spathulenol 7.73 %; glubulol 5.58 %; beta-eudesmol 4.04 %; in essential oil of C. antiochia var. antiochia caryophyllene 18.23 %; germacrene 27.37 %; spathulenol 29.86 %; hexadecanoic acid 7.21 % and in essential oil of C. albonitens gamma-elemene 4.45 %; caryophyllene 7.75 %; germacrene 9.23 %; spathulenol 7.97 %; caryophyllene oxide 16.45 %; cembrene 6.25 %; phytol 4.75 %; beta-selinenol 4.57 % were the main constituents.
Keywords: Centaurea kurdica; C. antochia var antochia; C. albonitens essential oil; GC/MS; Compositae; Chemistry